QUALITY ASSESSMENT OF VARIOUS BRANDS OF CEFIXIME 400 MG CAPSULES AVAILABLE IN YEMENI MARKET - AL-GHANI, AHMED M.; ALKHAWLANI, MOHAMMED; ALWOSABI, AMIN; ALBEGALI, ABDULLAH A.; THABET, ANES A. M. (International Journal of Applied Pharmaceutics, 2025)
Objective: The study aimed to assess the quality control of different brands of cefixime 400 mg capsule brands available in Yemeni drug market. Methods: The pharmacopeial specifications of five cefixime 400 mg capsule brands available in Yemeni drug market, including two domestic brands, were assessed in this study. Assessment included assay content, capsule weight variation and disintegration. In addition, drug dissolution and antimicrobial activity test were assessed. Results: Out of five brands, three brands of cefixime 400 mg capsules passed official specified assay tests according to United States Pharmacopeia (USP) specifications. The five brands showed a similar profile of weight variation and drug disintegration that were within the limits. However, the results of drug content for five brands showed in range 78.78-104.46 % in which three brands (B, D and E) in compliance to USP specifications (90-110%) and two brands (A and C) not compliance to USP specification. Also, the results of dissolution profile were in range 86.2-109.8% for four brands (A, B, D and E) that compliance to USP specifications, and 73.56% for brand C that was not compliance to USP specifications. Conclusion: Based on the results obtained in this study, the drug content for three brands (B, D, E) is within the pharmacopeial limit, but the drug content of (A, C) is out of the limit. while the capsule disintegration, weight variations, and antibacterial activity in all tested brands are within the pharmacopeial limit. The dissolution profile for four brands (A, B, D, E) is within the pharmacopeial limit, but the dissolution profile for (C) is less than the allowed limit.